2022
DOI: 10.1155/2022/1183436
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Management of the Health Status of Patients with Stable Chronic Obstructive Pulmonary Disease Treated with Double Bronchodilator

Abstract: Objective. To investigate the patients with stable chronic obstructive pulmonary disease (COPD) to understand the use of double bronchodilator therapy and influencing factors. Methods. The patients with stable COPD who used double bronchodilators were continuously enrolled in our hospital. The information of demographic characteristics, medical history, physical examination, drug use, and correct treatment methods after using inhaled drugs were collected by standardized questionnaire. Measurement data between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“… 21 LABA/LAMA therapy has been shown to improve lung function and reduce exacerbation rates without an increase in adverse effects, 21 , 22 but among patients with severe stable COPD treated with fixed-dose combination LABA/LAMA therapy, correct use was only reported in approximately 60%. 23 In the REAL study, ICS/LABA + LAMA use was higher in patients with more severe disease, although not when disease severity was categorized according to GOLD 2017. This suggests that the physician’s decision to step-up to triple therapy was driven by severity of lung function rather than acute exacerbation risk.…”
Section: Discussionmentioning
confidence: 93%
“… 21 LABA/LAMA therapy has been shown to improve lung function and reduce exacerbation rates without an increase in adverse effects, 21 , 22 but among patients with severe stable COPD treated with fixed-dose combination LABA/LAMA therapy, correct use was only reported in approximately 60%. 23 In the REAL study, ICS/LABA + LAMA use was higher in patients with more severe disease, although not when disease severity was categorized according to GOLD 2017. This suggests that the physician’s decision to step-up to triple therapy was driven by severity of lung function rather than acute exacerbation risk.…”
Section: Discussionmentioning
confidence: 93%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%